Treatment modalities in sinonasal undifferentiated carcinoma: an analysis from the national cancer database. Issue 2 (7th October 2016) - Khan, Mohemmed N.; Konuthula, Neeraja; Parasher, Arjun; Genden, Eric M.; Miles, Brett A.; Govindaraj, Satish; Iloreta, Alfred M.
Abstract : Background: Sinonasal undifferentiated carcinoma (SNUC) is a rare, aggressive malignancy of unknown etiology with a poor overall prognosis. Its relative rarity has made it difficult to determine the impact of different treatment modalities on survival. Methods: Retrospective study of cases in the National Cancer Data Base (NCDB). NCDB cases that were diagnosed as having SNUC between January 1, 2004, and December 31, 2013 were included in the analysis. Outcomes of patients treated with surgery followed adjuvant chemoradiotherapy were compared with definitive chemoradiotherapy. Results: A 5‐year survival rate of 42.2% was observed in the 460 patients in the analysis. American Joint Committee on Cancer (AJCC) clinical staging data were available for 304 patients. Of these patients, 60.2% had advanced tumors (AJCC stage 3 or 4). Surgery followed by adjuvant chemoradiotherapy was associated with better survival than definitive chemoradiotherapy (55.8% vs 42.6%, p = 0.007) in the study population. However, in late‐stage tumors, there was no difference in survival between the 2 treatment groups ( p = 0.22). For late‐stage tumors, the time to initiation of adjuvant therapy was 49.2 ± 5.1 days for the surgery plus adjuvant therapy group as compared with 25.9 ± 2.6 days in the definitive chemoradiotherapy group ( p < 0.0001), yet this did not appear to affect outcomes. No differences in age, gender, race, Charlson‐Deyo score, facility type (academic vs nonacademic), or radiation dose were found between the 2 treatment groups ( p > 0.05). Margin status played a critical role in the success of surgical resection, as no patients with positive margin status receiving adjuvant therapy survived to 5 years. Conclusion: Surgery may play a role in a multimodality approach to treatment of late‐stage SNUC if the tumor is amenable to surgical resection and negative margins can be reliably obtained. However, in cases where there may be difficulty obtaining negative margins, or this is considered unlikely preoperatively, surgical resection does not appear to provide any additional survival benefit.